Antimicrobial properties of plant fibers for biomedical applications - Miño Toro, Karla Wanda (2019)
Nowadays, in the world of materials, there is an increasing demand for biopolymers that replace their synthetic pairs. One alternative is plant fibers, which are largely used by its availability, biocompatibility and degradability characteristic. However, antimicrobial properties of plant fibers have not been reported, usually, this biopolymer is modified with antibacterial agents, metals or blends to give it antimicrobial activity. The objective of this research was to test fibers from several plants to find antimicrobial properties based on physical, chemical and morphological characteristics. For this purpose, the plant fibers were characterized in order to know their structure and composition using common techniques such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). Antimicrobial and inhibitory tests were performed against Escherichia coli in Yachay Tech. The results indicate two of seven fiber studied shown inhibitory properties, this research could have a significant impact on biomedical applications.